Freedom in the Anthropocene - Stoner, A. author. aut Link
X, 125 p.
Keywords: Freedom in the Anthropocene illuminates the Anthropocene from the perspective of critical theory. The authors contextualize our current ecological predicament by focusing on the issues of history and freedom and how they relate to our present inability to render environmental threats and degradation recognizable and surmountable.